Agricultural management economics : - Rae, Allan N. (CAB International, 1994)
This book on agricultural management and decision making differs from other texts which tend to describe production economics followed by the presentation of analytical approaches. Instead, the processes of agricultural production and their management are couched in terms of activity analysis, since this permits greater integration of theory with practical evaluations.